2017
DOI: 10.1007/s00415-017-8484-1
|View full text |Cite
|
Sign up to set email alerts
|

Capturing saccades in multiple sclerosis with a digitized test of rapid number naming

Abstract: The King–Devick (K–D) test of rapid number naming is a visual performance measure that captures saccadic eye movements. Patients with multiple sclerosis (MS) have slowed K–D test times associated with neurologic disability and reduced quality of life. We assessed eye movements during the K–D test to identify characteristics associated with slowed times. Participants performed a computerized K–D test with video-oculography. The 25-Item National Eye Institute Visual Functioning Questionnaire (NEI-VFQ-25) and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…These findings may be in accordance with prior studies, which suggest that not only may LCLA better capture visual dysfunction in MS than HCVA, but also that LCLA may be a more encompassing and reliable biomarker and outcome reflective of the MS disease process [28]. Additionally, our study findings support preliminary studies that found associations between LCLA and cognitive function in a small sample of RRMS and SPMS patients [11], and decreased visual-cognitive performance in MS measured by the King-Devick test [29]. Importantly, similar relationships within the visual-cognition axis have been implicated in other neurological disorders, including Alzheimer’s disease [30] and Parkinson’s disease [31].…”
Section: Discussionsupporting
confidence: 84%
“…These findings may be in accordance with prior studies, which suggest that not only may LCLA better capture visual dysfunction in MS than HCVA, but also that LCLA may be a more encompassing and reliable biomarker and outcome reflective of the MS disease process [28]. Additionally, our study findings support preliminary studies that found associations between LCLA and cognitive function in a small sample of RRMS and SPMS patients [11], and decreased visual-cognitive performance in MS measured by the King-Devick test [29]. Importantly, similar relationships within the visual-cognition axis have been implicated in other neurological disorders, including Alzheimer’s disease [30] and Parkinson’s disease [31].…”
Section: Discussionsupporting
confidence: 84%
“…Professional equipment is usually necessary to perform quantitative analysis of SPEM. Though such devices can be purchased, and published studies have reported using them [12], they are expensive and impractical for routine use during medical treatment. Our investigation, however, used commercially available equipment and free software to construct a cheap, effective system: a commercially available infrared CCD camera and a PC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we make small intraline saccades and large interline saccades during reading. Recent studies showed that chronic concussion patients and multiple sclerosis patients made more saccades to complete a rapid number naming test, and these extra saccades appear to be small (Hainline et al, 2017 ; Rizzo et al, 2016 ). As shown in the Results section, the conventional SG filter tends to underestimate the peak velocity of saccades, especially small-amplitude saccades.…”
Section: Discussionmentioning
confidence: 99%